Detection of Evolution and Adaptation Fingerprints in Metabolic Networks - Güell, Oriol (A Network-Based Approach to Cell Metabolism, 2017)
Metabolic fluxes present an heterogeneity that can be exploited to construct metabolic backbones as reduced versions of metabolic networks. These backbones can be analysed to extract important biological information. In this chapter, the disparity filter is applied to two organisms, Escherichia coli and Mycoplasma pneumoniae. Backbones offer information about long-term evolution since they contain the core of ancestral pathways related with energy obtainment optimized by evolution to maximize growth. At the same time, backbones unveil short-term adaptation capabilities to variable external stimuli.